Analysis on Customer Authentic Perception on Fast-Food Chain’s Brand Loyalty with the Mediation Variables being Perceived Quality - Robby Kurniawan; Stevannie Chang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to examine the impact of fast-food restaurants brands toward tourist’s restaurants authentic perception with the perceived quality as the mediating variables This study uses a quantitative approach to collect empirical data and conduct hypothesis testing. The population studied in this study consists of the population of Batam City. The methodology used in this study included selecting a sample from individuals who visited a fast food restaurant chain. Data collection occurred from Q4 to Q1 of 2022-2023, resulting in a total of 400 observations. The process of hypothesis testing was performed using the IBM SPSS Statistics software with the application of descriptive analysis, quantitative analysis, and classical assumption tests. It was found that the customer perception has significant impacts on quality variable, and it also has a significant and positive effect on customer loyalty. This suggests that consumers consider the perception they received influenced the perceived quality of the restaurants they purchase from when they decide to continue to order from them in the future. The results of this study reveal the key aspects of service quality that have the greatest impact on customer loyalty. Factors such as punctuality, accuracy, responsiveness, and staff courtesy have been proven to be important factors in customer loyalty. Therefore, it is essential for fast food restaurants to continuously invest in improving these aspects to improve the quality of their service and thereby gain customer loyalty.